Aplicação de material de mudança de fase como armazenador de energia térmica em sistema de secagem solar - Silva, Thiago Aurélio Arruda (2021)
The drying process has been employed by human beings since the dawn of civilizations and it has become essential in industrial and food preservation processes. Among the drying methods, solar drying has been commonly discussed in the literature in recent years as a sustainable and low-cost option, despite its disadvantages, especially due to its intermittent nature. As a measure to mitigate this limitation, heat storage systems are applied in solar drying in order to accumulate heat during the day and continue dehydration at night or cloudy periods. Latent accumulation has been shown to be promising through the use of so-called phase change materials. Among these products, biological materials such as vegetable waxes stand out, as they are a sustainable alternative to paraffin. Brazil, being a country with a high incidence of solar irradiation, has the potential for solar drying through heat storage. In view of this, the general objective of the present work was to study the application of biological phase change materials in solar drying, in the Brazilian Midwest region. In order to meet the specific objectives, this work was divided into three chapters, as follows: Chapter 01 – assess the feasibility of using biological phase change materials in solar drying systems; Chapter 02 – evaluate the performance of a solar dryer with a latent heat thermal energy storage system, based on biological material; Chapter 03 – determine the drying kinetics curves of native product, with latent heat accumulation in solar drying and recommend a better fit mathematical model. The first study evaluated the use of type 3 carnauba, soy, palm and paraffin waxes as latent heat storage. Palm wax proved to be more promising for this purpose, with a melting temperature range more adjusted to solar drying, accumulating 239.04 J per gram of product. The second chapter addressed the construction and evaluation of the thermal performance of a conventional indirect solar dryer and one with heat storage, based on palm wax. In this, the dryer with thermal storage system, presented, on the day of best performance, the maximum temperature of 82.7 °C, average thermal efficiency of 103.97% and average mass efficiency of 67.68%. In the third chapter, nine mathematical models were adjusted to the data of drying kinetics of cashew nuts, in a solar dryer with thermal energy storage, using palm wax, and in a conventional indirect solar dryer. The Diffusion Approximation model better fit the drying curves of the first equipment, while Cavalcanti and Mata's model fits the second one. On June 15th and 16th, the dryer with storage showed higher estimated drying rates than the dryer with the absence of this thermal mechanism. Finally, the drying method, with thermal energy storage, based on biological phase change materials, demonstrated superior characteristics to paraffin, especially with regard to palm wax. This wax had a greater adaptation to the climatic conditions of the Midwest Region. The dryer with palm wax presented better performance, being possible to be used in products from family farming.